Democratic authority and the separation of church and state - Audi, Robert (Oxford University Press, 2011)
The autonomy of ethics and the moral authority of religion -- The liberty of citizens and the responsibilities of government -- The secular state and the religious citizen -- Democratic tolerance and religious obligation in a globalized world